UTILIZATION OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN MATHEMATICS LEARNING - Saadati, Farzaneh; Tarmizi, Rohani Ahmad; Ayub, Ahmad Fauzi Mohd (Journal on Mathematics Education, 2014)
Attention to integrate technology in teaching and learning has provided a major transformation in the landscape of education. Therefore, many innovations in teaching and learning have been technology-driven. The study attempted to examine what is engineering students’ perception regarding the use of Information and Communication Technologies (ICT) in mathematics learning as well as investigate their opinion about how ICT can be integrated to improve teaching and learning processes. The subjects were Iranian engineering students from two universities. The finding showed they are fully aware of importance of ICT in teaching and learning mathematics. Whilst, they were feeling comfortable and confident with technology, they do not have more experience of using technology in mathematics classes before. The findings supported the other studies, which indicated the potentials of ICT to facilitate students’ learning, improve teaching, and enhance institutional administration as established in the literature.Keywords: Technology, Mathematics Learning, Facebook, Attitude Toward ICT DOI: http://dx.doi.org/10.22342/jme.5.2.1498.138-147